Peripheral Blood Monocytes With an Antiinflammatory Phenotype Display Limited Phagocytosis and Oxidative Burst in Patients With Visceral Leishmaniasis. (19th July 2018) - Singh, Neetu; Kumar, Rajiv; Chauhan, Shashi Bhushan; Engwerda, Christian; Sundar, Shyam
Abstract : Blood monocytes from patients with visceral leishmaniasis (VL) are skewed toward a disease-promoting antiinflammatory phenotype. They have a reduced phagocytic capacity and limited ability to generate microbicidal molecules. These finding may help improve therapeutic options for VL treatment. Abstract: Background: Monocytes are important effector cells during Leishmania infection, and changes in their functions may impact development of immunity. However, functional characteristics of monocytes in patients with visceral leishmaniasis (VL) remains poorly understood. Methods: Peripheral blood monocytes from patients with VL and healthy endemic controls from Muzaffarpur, India, were isolated and compared in an ex vivo setting, using cell-culture techniques, flow cytometry, and reverse transcription quantitative polymerase chain reaction analysis. Results: A blood monocyte population with a gene signature comprising upregulated expression of TGM2, CTLRs, VDR, PKM, SOCS1, and CAMP1 and downregulated expression of NOS2 and HIF1A was observed in patients with VL but not in controls. Monocytes from patients with VL also had impaired expression of chemokine receptors and adhesion molecules and decreased frequencies of interleukin 1β– and interleukin 6–producing cells. Importantly, monocytes from patients with VL had a markedly reduced capacity for phagocytosis of amastigotes, p47phox and p67phox expression, and reactive oxygen species production. Conclusions: Monocytes from patients with VL express antiinflammatory molecules and lack a classically activated phenotype. They have reduced expression of molecules related to activation and antiparasitic effector functions, indicating that monocytes are skewed toward an antiinflammatory phenotype. These findings provide insights into the functional status of monocytes during VL and advise that therapeutic manipulation of this important cell population may result in favorable patient outcomes.